The Characteristics, Knowledge, and Attitude of Pregnant Women Regarding Early Breastfeeding Initiation on the Fourth Antenatal Care Visit - Elsa Pudji Setiawati; Cindy Regina Putri; Tisnasari Hafsah (Faculty of Medicine Universitas Padjadjaran, 2020)
Background: Early breastfeeding initiation within one hour after birth can reduce maternal and neonatal mortality. One of the interventions given on the fourth antenatal care (ANC) visit is providing information regarding breastfeeding initiation, however, the implementation is low. Many factors may influence breastfeeding initiation, including knowledge and attitude. The aim of this study was to analyze the relationship among the characteristics, knowledge, and attitude of the pregnant women on the fourth ANC visit regarding early breastfeeding initiation in Jatinangor.Methods: An analytic cross-sectional study was conducted in September 2013. A total of 61 pregnant women registered for the fourth ANC visit (K4) in Jatinangor Public Health Center were involved in this study. Data were collected from questionnaires. Data on the number of gestation, level of education, source of information regarding breastfeeding initiation, knowledge and attitude about early breastfeeding initiation were collected and analyzed using chi-square.Results: There was a significant relationship between a number of gestation, level of education, source of information and knowledge also attitude, as well as between age and attitude (p<0.05). However, there was no significant association between age and knowledge (p>0.05).Conclusions: Number of gestation, level of education, and source of information have a significant relationship with both knowledge and attitudes about early breastfeeding initiation.